Physical activity affects DNA methylation-derived inflammation markers in a community-based Parkinson's disease study - Yang Cheng Hu; Keren Zhang; Kimberly C. Paul; Jin Zhou; Jeff M. Bronstein; Cynthia D.J. Kusters; Beate R. Ritz (Brain, Behavior, & Immunity - Health)
Introduction: Past studies have connected physical activity (PA) and Parkinson's disease (PD) to chronic inflammation. We use DNA methylation-derived (DNAm) proxies for inflammation to investigate the relationship between PA and chronic inflammation among PD patients. Methods: We collected demographics, lifestyle, and PA status information by interviewing 555 PD patients enrolled in the Parkinson's Environment and Gene (PEG) studies. We used the epigenetic clock website to generate DNAm proxies and performed principal component analysis (PCA) of 22 DNAm cytokine proxies. Using the Mann-Whitney U test, we compared the PC scores of active and sedentary patients. For PCs associated with PA status, we examine associations between PA status, the amount of PA, and PCs for DNAm cytokines using permutation-based tests. Results: Compared to sedentary PD patients, those who reported strenuous PA have lower levels of c-reactive protein (CRP; p < 0.01) and higher levels of Fc receptor-like 2 (FcRL2; p = 0.02). Patients who engaged in moderate PA have lower levels of C-X-C motif chemokine ligand 9 (CXCL9; p = 0.03), 10 (CXCL10; p = 0.02), and 11 (CXCL11; p = 0.01). Among active patients, strenuous PA is non-linearly (convex-shape) associated with the proportions of natural killer cells (NK; p = 0.02) and CD8T cells (p = 0.05) and negatively associated with CRP levels (p = 0.02). We also observe a non-linear association between moderate PA and monocyte counts (p = 0.02). Conclusion: PA may benefit PD patients by reducing chronic inflammation. We also found that strenuous PA may increase the proportions of NK and CD8T cells, though further effort is needed to confirm potential shifts in immune cell subtypes.